Elaboración de galletas de té matcha como fuente adicional de fibra y de antioxidantes (2020)
Nowadays, matcha tea is a high quality ingredient due to its dietary fiber and antioxidant content, which lead to the development of a daily intake product such as cookies. In this case three types of flour were used: oat, almond and chia along with three different concentrations of matcha tea (0% w/w, 5% w/w, 10% w/w). In order to verify polyphenol, antioxidant and dietary fiber content a bibliographic research was implemented, providing data from different climatic conditions and processing. To evaluate the main physical properties of the cookies some tests such as moisture, hardness and shelf life were implemented, besides performing viscosity tests for each of the cookie doughs. In order to determinate the market and the customer profile...